2017
DOI: 10.1097/ta.0000000000001502
|View full text |Cite
|
Sign up to set email alerts
|

Incremental balloon deflation following complete resuscitative endovascular balloon occlusion of the aorta results in steep inflection of flow and rapid reperfusion in a large animal model of hemorrhagic shock

Abstract: Introduction To avoid potential cardiovascular collapse after Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA), current guidelines recommend methodically deflating the balloon over 5 minutes to gradually reperfuse distal tissue beds. However, anecdotal evidence suggests that this approach may still result in unpredictable aortic flow rates and hemodynamic instability. We sought to characterize aortic flow dynamics following REBOA as the balloon is deflated in accordance with current practice g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…The biggest impact of AO on SBP for patient 2 was noticed when the last milliliter was removed from the balloon, suggesting first an important role of partial AO on the stability of the patient and second a nonlinear correlation between AO and SBP. This observation has actually been described by Davidson et al [ 38 ] in a swine model where a steep inflection point occurs during balloon deflation that results in an abrupt increase in aortic flow and a concomitant decrease in mean arterial pressure. Furthermore, the onset of distal aortic flow was inconsistent across study animals and did not correlate with initial balloon volume or relative deflation volume.…”
Section: Discussionsupporting
confidence: 74%
“…The biggest impact of AO on SBP for patient 2 was noticed when the last milliliter was removed from the balloon, suggesting first an important role of partial AO on the stability of the patient and second a nonlinear correlation between AO and SBP. This observation has actually been described by Davidson et al [ 38 ] in a swine model where a steep inflection point occurs during balloon deflation that results in an abrupt increase in aortic flow and a concomitant decrease in mean arterial pressure. Furthermore, the onset of distal aortic flow was inconsistent across study animals and did not correlate with initial balloon volume or relative deflation volume.…”
Section: Discussionsupporting
confidence: 74%
“…These changes are too precise to be performed manually with any manner of fidelity or consistency, thereby necessitating robotic control. As we have demonstrated in prior experiments and again in the present experiment, very small adjustments in the degree of aortic occlusion translate into large variations in aortic flow rate [12,15]. Hyperemic aortic flow was again observed during the balloon deflation phase of this experiment and likely reflects the hyperdynamic cardiac state induced by aortic occlusion, combined with low systemic vascular resistance from vasodilated distal tissue beds.…”
Section: Discussionsupporting
confidence: 83%
“…Hyperemic aortic flow was again observed during the balloon deflation phase of this experiment and likely reflects the hyperdynamic cardiac state induced by aortic occlusion, combined with low systemic vascular resistance from vasodilated distal tissue beds. This hyperemic flow is fairly unpredictable in its onset and occurs at different balloon volumes depending on the individual animal [12]. Therefore, establishing clinical guidelines for manual balloon deflation based on a prescribed volume is not practical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an animal study conducted on eight swine models of hemorrhage found that graded balloon deflation still led to a rapid increase in aortic flow followed by a decrease in proximal mean arterial pressure. Furthermore, the time required for return of distal aortic flow was variable and inconsistent across the subjects [ 27 ].…”
Section: Resultsmentioning
confidence: 99%